THE NOTIONS OF COGNITIVE LINGUISTICS - Kamola Aripova Yusupovna (Journal of new century innovations, 2024)
Cognitive linguists like other linguists, study language for its own sake; they attempt to describe and account for its systematicity, its structure, the functions it serves and how these functions are realised by the language system. However, an important reason behind why cognitive linguists study language stems from the assumption that language reﬂects patterns of thought. Therefore, to study language from this perspective is to study patterns of conceptualisation. Language oﬀers a window into cognitive function, providing insights into the nature, structure and organization of thoughts and ideas. The most important way in which cognitive linguistics diﬀers from other approaches to the study of language, then, is that language is assumed to reﬂect certain fundamental properties and design features of the human mind. As we will see throughout this book, this assumption has far-reaching implications for the scope, methodology and models developed within the cognitive linguistic enterprise. Not least, an important criterion for judging a model of language is whether the model is psychologically plausible.